Balancing act: the effects of race and poverty on LIHTC development in Boston. Issue 7 (8th August 2020) - Shamsuddin, Shomon; Cross, Hannah
Abstract: The debate about where to build affordable housing remains unresolved. Fair housing advocates encourage placement in low poverty neighborhoods while community development proponents support the opposite approach. Prior work notes the Low-Income Housing Tax Credit (LIHTC) program is disproportionately found in Black and poor areas but the results are based on 20-year old data and ignore effects within LIHTC neighborhoods. This paper uses recent data and multivariate analysis to explore the impact of neighborhood racial composition and poverty rate on LIHTC development in the Boston metropolitan region. We find race is associated with the presence of LIHTC development while poverty is associated with the amount of LIHTC housing built, which reveals important differences between project siting and size. LIHTC units are not more heavily concentrated in Black or poor neighborhoods, conditional on LIHTC development. The findings suggest how the LIHTC program can be used to balance competing fair housing and community development priorities in developing affordable housing.